Strategi Kepemimpinan Kepala Sekolah Dalam Pengembangan Kompetensi Profesional Guru untuk Peningkatkan Mutu Pendidikan di SMK Cendikia Muslim Kabupaten Bogor - Awaludin Awaludin (Jurnal Dirosah Islamiyah, 2020)
ABSTRACT This study to provide an overview of the leadership of school principle in the development of professional competence and teacher for improving the quality of eduation in Cendikia Muslim Vocational School Bogor, which is explained in depth, the procedures and concrete steps of the principal’s leadership in developing professional competence to improve the quality of education in the Cendikia Muslim Vocational School in Bogor as well as in factors and supporting the role of the principal’s leadership in developing the professional competence of teachers in the Cendikia Muslim Vocational School in Bogor. This research is a form of field research that is descriptive qualitative, using several approaches namely, pedagogical, sosiological, psychological and managerial. The author also uses several instruments to including observation, documentation, and interviews. The type of data needed in this study are primary data and secondary of teachers to improvedata. While the data collection techniques used are observation, interviews, and documentation referring to the deductive and inductive analysis using several methods that are relevant to the main variables to be studied, while the informant as the resource person is the principal, the teacher. Based on this research it can be concluded that the Principal's Strategy and Leadership in developing professional competence of teachers to improve the quality of education that the leadership of the Head of the Bogor Cendikia Muslim Vocational School in carrying out their duties responsibly, to improve teacher competency and professionalism, by conducting a normative approach or providing motivation teachers to always work in accordance with their duties, with expertise in the field of study being taught. The procedure desired by the principal in improving teacher competency and professionalism is to supervise the deliberation, communication, planning, coordination and evaluation approach, with this application finally all intentions will be realized. To overcome the inhibiting factors in the implementation of education, especially the success of school principals in improving teacher competency and professionalism, it is expected that the unity of steps and togetherness of the goals of all school components including headmasters, teachers, students, and parents and the surrounding community will jointly implement their vision and mission at Cendikia Muslim Vocational School Bogor Keywords: Leadership and Principal Strategies and Teacher Professional Competence